Sleep evaluation scales and questionnaires: A review (2008)
Introduction. Whenever a new scale is created or translated from another language, it must be validated, establishing its reliability for the new population where it will be used. Sleep quality concept is a construct that can be evaluated using self-report scales. Resulting elements vary depending on the individuals surveyed. This type of evaluation is mainly subjective and includes quantitative aspects such as sleep duration, number of awakenings, latency time, and qualitative aspects such as rest sensation, mood and oneiric content (Valencia, 2000). In the present study we made a critical review of the sleep scales designed for child, adolescent and adult populations that have been validated and the difficulties they might present. Methodology. Between September 2005 and May 2006 a bibliographical search was made within pubmed, ovid, and the data base of the periodical and book library of the Ramón de la Fuente Muñiz National Institute of Psychiatry, using and combining the following key words: sleep, sleep questionnaire, sleep scale, sleep inventory, adolescent, adolescent sleep scale. The most relevant papers to our study were selected. The search was limited to Spanish and English articles, although there was no year or geographical origin limit. Articles that did not include clinimetrical data where excluded. Conclusions. Based on our bibliographical search and our discussion, we suggested the design and validation of a Spanish scale to evaluate adolescent population which avoids a time interval between awakening and the answering of the instrument in order to decrease recall bias.